Reconstructing 90 years of anthropogenic activities in a subtropical reservoir: a chemometric and paleolimnological perspective - Cardoso-Silva, Sheila [UNESP]; Kim, Bianca Sung Mi; de Lima Ferreira, Paulo Alves; Benedetti, Beatriz; Goyenola, Guillermo; Iglesias, Carlos; Figueira, Rubens Cesar Lopes; López-Rodríguez, Anahí; Moschini-Carlos, Viviane [UNESP]; de Mello, Franco Teixeira; Meerhoff, Mariana; Pompêo, Marcelo (Springer Nature, 2024)
Environmental reference conditions (RC) and historical trends are crucial for assessing the degree of freshwater impact and formulating restoration measures. This is particularly relevant for freshwater systems used as potable water sources. Using sediments from the Carlos Maggiolo reservoir (Minas, Uruguay), located in a watershed with a mining history, this study aimed to (1) establish metal (As, Cr, Cu, Ni, Pb, and Zn) RC using a predicted interval (PI) chemometric technique; (2) evaluate metal enrichment and toxicity over time and space; and (3) assess environmental changes examining geochemical proxies. Surface sediments from 29 stations were used to establish RC and a core from the dam area was sampled to infer past conditions. The sediments were submitted to partial digestion and analyzed by inductively coupled plasma optical emission spectrometry- ICP-OES. Enrichment factor (EF) calculated using both PI and bottom core values did not show significant differences over time. Over space and time, most metals primarily originated from natural sources (EF < 2). The PI in mg/kg was Cr: 23.74–37.32; Cu: 25.75–48.99; Ni: 16.29–25.55; Pb: 7.63–13.75; and Zn: 94.34–174.80. A stratigraphically constrained cluster analysis corroborated by a permutational multivariate analysis of variance categorized the reservoir into two zones: Zone I, before reservoir operation to ~ 1996, and Zone II from ~ 1997 to 2017. The average concentrations of the main metals of toxicological interest in zones I and II, respectively, were as follows: Cr 37.60 ± 1.59, 34.54 ± 1.49 mg/kg; Cu 49.76 ± 2.84, 44.55 ± 2.70 mg/kg; Ni 24.11 ± 0.67, 22.53 ± 1.22 mg/kg; Pb 12.40 ± 0.63, 13.52 ± 0.82 mg/kg; Zn 99.25 ± 3.12, 93.86 ± 4.42 mg/kg; Mn 1160.56 ± 68.88, 1441.61 ± 83.55 mg/kg; and P 1243.21 ± 271.56, 1128.42 ± 183.10 mg/kg. According to a principal component analysis, the period preceding reservoir operation until ~ 1985 was linked to mining activities and application of Cu2SO4, and the period from 1985s to 2000 was influenced by C and P concentrations due to increasing agricultural and afforestation activities in the watershed that consume P fertilizers. The most recent period, from 2000 to ~ 2017, was characterized by an increase in sedimentation rates mainly associated with erosion, particularly in the agricultural areas. This subsequent soil loss in the watershed could compromise the reservoir's useful life. This study contributes to a better understanding of metal geochemistry in subtropical reservoirs and aids in formulating effective recovery and restoration measures.
Keywords: Chemometric; Drinking water; Enrichment factor; Paleolimnology; Reference condition; Sediment rate